Integration‐Free Induced Pluripotent Stem Cells Model Genetic and Neural Developmental Features of Down Syndrome Etiology123. (25th February 2013) - Briggs, James A.; Sun, Jane; Shepherd, Jill; Ovchinnikov, Dmitry A.; Chung, Tung‐Liang; Nayler, Sam P.; Kao, Li‐Pin; Morrow, Carl A.; Thakar, Nilay Y.; Soo, Set‐Yen; Peura, Teija; Grimmond, Sean; et al.
Abstract Down syndrome (DS) is the most frequent cause of human congenital mental retardation. Cognitive deficits in DS result from perturbations of normal cellular processes both during development and in adult tissues, but the mechanisms underlying DS etiology remain poorly understood. To assess the ability of induced pluripotent stem cells (iPSCs) to model DS phenotypes, as a prototypical complex human disease, we generated bona fide DS and wild‐type (WT) nonviral iPSCs by episomal reprogramming. DS iPSCs selectively overexpressed chromosome 21 genes, consistent with gene dosage, which was associated with deregulation of thousands of genes throughout the genome. DS and WT iPSCs were neurally converted at >95% efficiency and had remarkably similar lineage potency, differentiation kinetics, proliferation, and axon extension at early time points. However, at later time points DS cultures showed a twofold bias toward glial lineages. Moreover, DS neural cultures were up to two times more sensitive to oxidative stress‐induced apoptosis, and this could be prevented by the antioxidant N‐acetylcysteine. Our results reveal a striking complexity in the genetic alterations caused by trisomy 21 that are likely to underlie DS developmental phenotypes, and indicate a central role for defective early glial development in establishing developmental defects in DS brains. Furthermore, oxidative stress sensitivity is likely to contribute to the accelerated neurodegeneration seen in DS, and we provide proof of concept for screening corrective therapeutics using DS iPSCs and their derivatives. Nonviral DS iPSCs can therefore model features of complex human disease in vitro and provide a renewable and ethically unencumbered discovery platform. STEM CELLS2013;31:467–478